Synthesis and solid-state structural characterization of di-μ-azido-bis[{azido(N, N-diethylethylenediamine)}copper(II)] - Casagrande Jr., Osvaldo L. [UNESP]; Klein, Stanlei Ivair [UNESP]; Mauro, Antonio Eduardo [UNESP]; Tomita, Koychi [UNESP] (Springer Nature, 1989)
The 1:1 mixed-ligand [{Cu(N3)2(diEten)}2] (diEten=N,N-diethylethylenediamine) complex has been synthesized and characterized by i.r. spectroscopy and X-ray diffraction. The compound crystallizes in the triclinic space group P1. Its structure consists of a centrosymmetric Cu2N2 unit whose N atoms belong to end-on azido bridges. Each copper atom is also surrounded by three nitrogen atoms; two from one N, N-diethylethylenediamine, and one from the remaining azide. The five nitrogen atoms altogether occupy the vertices of a slightly distorted trigonal bipyramid, and the azidobridges produced a rather short Cu...Cu distance of 3.37 Å. © 1989 Chapman and Hall Ltd.